2011
DOI: 10.5372/1905-7415.0502.035
|View full text |Cite
|
Sign up to set email alerts
|

Elastic bandage vs. neoprene thumb stabilizer splint in acute De Quervain’s tenosynovitis

Abstract: Background: De Quervain’s tenosynovitis is a common disease among the patients who performed unaccustomed repetitive movement of the thumb side of the wrist. A neoprene thumb stabilizer splint is often used to restrict thumb movement. However, because of its cost, usage of an elastic bandage made of cheaper materials is proposed. Objective: Compare the effectiveness between the elastic bandage and the neoprene thumb stabilizer splint in acute De Quervain’s tenosynovitis. Methods: Forty participants wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…A total of 37 studies were initially found to be eligible. Of those, 7 studies did not include 1 of our predefined outcome measures or included patients with conditions other than DQT and did not analyze data separately and were therefore excluded (Figure 1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A total of 37 studies were initially found to be eligible. Of those, 7 studies did not include 1 of our predefined outcome measures or included patients with conditions other than DQT and did not analyze data separately and were therefore excluded (Figure 1).…”
Section: Resultsmentioning
confidence: 99%
“…A total of 37 studies 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 were initially found to be eligible. Of those, 7 studies 9 , 10 , 11 , 12 , 13 , 14 , 15 did not include 1 of our predefined outcome measures or included patients with conditions other than DQT and did not analyze data separately and were therefore excluded ( Figure 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…All patients in both groups had some aggravating factor but relieving factors were less. It has been reported that 8.3% of patients present with upper extremity conditions as their chief complaint in chiropractic practices [12,13]. De Quervain's has also been shown to usually present in the fifth and sixth decades of life, as well as being more common in pregnant and lactating women.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that 8.3% of patients present with upper extremity conditions as their chief complaint in chiropractic practices. 12,13 De Quervain's has also been shown to usually present in the fifth and sixth decades of life, as well as being more common in pregnant and lactating women. The medication included nonsteroidal Anti-inflammatory Drugs (NSAIDs) and analgesic, an injection of a steroid mixed with xylocaine into tendon sheaths.…”
Section: Discussionmentioning
confidence: 99%